Strategi Persaingan Pemasaran Indomaret dan Alfamart di Salatiga Menggunakan Game Theory - Juli Christanto, Henoch; Aprius Sutresno, Stephen; Mavish, Steven; Afrianto Singgalen, Yerik; Dewi, Christine (Jurnal Elektro, 2023)
Indomaret and Alfamart are minimarket businesses that are currently experiencing significant growth, especially in the city of Salatiga. Each company strives to achieve maximum profit, and thus, it is essential to determine the most optimal competitive strategy to attract customers. This research was conducted using a questionnaire to understand what influences consumers in choosing a minimarket for shopping, providing valuable insights for determining minimarket strategies. Game Theory is employed to represent the respondents. The results of the study indicate that Alfamart will employ a location-based strategy in their stores, while Indomaret will utilize discount and promotion strategies for their easily accessible minimarkets.